Psychiatric emergencies during the height of the COVID-19 pandemic in the suburban New York City area. (April 2021) - Ferrando, Stephen J.; Klepacz, Lidia; Lynch, Sean; Shahar, Sivan; Dornbush, Rhea; Smiley, Abbas; Miller, Ivan; Tavakkoli, Mohammad; Regan, John; Bartell, Abraham
Abstract: Background: This report characterizes patients presenting for psychiatric emergencies during the COVID-19 pandemic and describes COVID-19-related stressors. Methods: Patients seen for emergency psychiatric evaluation during the height of the COVID-19 period (March 1-April 30, 2020; N = 201) were compared with those in the immediate Pre-COVID-19 period (January 1-February 28, 2020; N = 355), on sociodemographic characteristics, psychiatric diagnoses, symptoms, and disposition. Patients tested positive for COVID-19 were compared with those that tested negative on the same outcomes. Prevalence and nature of COVID-19-stressors that influenced the emergency presentation were rated. Outcome: The most common psychiatric diagnoses and presenting symptoms during both periods were depression and suicidal ideation. Comparing the Pre-COVID-19 and COVID-19 periods, a significant decline in emergency psychiatric volume was observed in children and adolescents (C/A), but not adults. COVID-19 period C/A patients had more new onset disorders and were more likely to be admitted to inpatient care, but were less likely to present with suicide attempts, impulse control disorders and agitation/aggression. Adults were more likely to have no access to outpatient care, present with anxiety disorders, and were also more likely to be admitted for inpatient care. COVID-19 directly affected the psychiatric emergency in 25% of patients, with the more severe stressors triggered by fear of COVID infection (including psychosis), actual COVID infection in self or family members, including death of a loved one. COVID-positive patients were more likely to have psychosis, including new-onset, and were less likely to be depressed/suicidal compared to their COVID-negative counterparts. Conclusion: This report demonstrates the need for emergency psychiatric services throughout the COVID-19 pandemic and the need for clinical and diagnostic COVID-19 screening of psychiatric emergency patients. New and severe pathology underscore the need for enhanced outpatient access to tele-mental health, crisis hotline and on-line psychotherapeutic services, as well as psychiatric inpatient services with capacity to safely care for COVID-19 patients.